2011
DOI: 10.4061/2011/304583
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Incorporation, Channel Formation, and Disruption of Calcium Homeostasis by Alzheimer′s β‐Amyloid Protein

Abstract: Oligomerization, conformational changes, and the consequent neurodegeneration of Alzheimer's β-amyloid protein (AβP) play crucial roles in the pathogenesis of Alzheimer's disease (AD). Mounting evidence suggests that oligomeric AβPs cause the disruption of calcium homeostasis, eventually leading to neuronal death. We have demonstrated that oligomeric AβPs directly incorporate into neuronal membranes, form cation-sensitive ion channels (“amyloid channels”), and cause the disruption of calcium homeostasis via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 157 publications
(141 reference statements)
4
70
0
Order By: Relevance
“…The effect of AβP was similar to that of gramicidin and amphotericin which are commonly used to perforate neuron membranes. Furthermore, we have revealed that AβP directly caused the disruption of liposomal membrane vesicles by observing the release of fluorescent dye (Kawahara et al, 2011b). These results are consistent with the findings that AßP causes membrane disruption, increases membrane permeability, causes hemolysis, and changes membrane fluidity (Eckert et al, 2005).…”
Section: Formation Of Ca 2+ Permeable Pores By Aßpsupporting
confidence: 80%
See 2 more Smart Citations
“…The effect of AβP was similar to that of gramicidin and amphotericin which are commonly used to perforate neuron membranes. Furthermore, we have revealed that AβP directly caused the disruption of liposomal membrane vesicles by observing the release of fluorescent dye (Kawahara et al, 2011b). These results are consistent with the findings that AßP causes membrane disruption, increases membrane permeability, causes hemolysis, and changes membrane fluidity (Eckert et al, 2005).…”
Section: Formation Of Ca 2+ Permeable Pores By Aßpsupporting
confidence: 80%
“…The conformational diseases includes prion diseases, triplet-repeat diseases, e.g., Huntington's disease, Parkinson's disease and other neurodegenerative diseases that can be categorized under dementia with Lewy bodies (DLB). Increasing evidence indicates that most of these disease-related amyloidogenic proteins or their peptide fragments are directly incorporated into membranes to form ion channels as well as AβP (Lashuel and Lansbury, 2002;Kawahara et al, 2011b). It was also demonstrated that AßP (1-40), α-synuclein, amylin, ABri, or other amyloidogenic peptides morphologically similar common ion channel-like structures and elicit single channel currents using AFM, CD, gel electrophoresis, and electrophysiological recordings (Quist et al, 2005;Lal et al, 2007).…”
Section: Disruption Of Calcium Homeostasis By Amyloid Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligomer cytotoxicity appears to result from the aberrant interactions of such species with the lipid bilayers, disrupting cell membranes and impairing their ability to maintain cellular homeostasis [14][15][16][17][18]. Several studies support the notion that membrane disruption induced by A␤ allows the entry of small molecules and ions, mainly free Ca 2+ ions [19][20][21][22]. In particular, it was reported that A␤ can induce a generalized thinning of the phospholipid bilayer, thereby resulting in perturbation of Ca 2+ fluxes [23].…”
Section: Introductionmentioning
confidence: 96%
“…A common hypothesis used to explain the toxicity induced by A␤ is the formation of amyloid pores in the plasma membrane. Regarding this, several studies from our and other laboratories support the notion that membrane disruptions are induced by A␤ [6][7][8][9][10][11][12][13]. Furthermore, A␤ perforation allows the entry of small molecules and ions, such as calcium, into the cells [6,7,12].…”
Section: Introductionmentioning
confidence: 84%